Eco-digital Indonesian language in elementary education: Ecological interest and technological perception - Mundakir Mundakir; Ade Hikmat; Siti Zulaiha (BAHASTRA, 2026)
A This study examines the relationship between ecological interest and technological perception in shaping elementary students’ support toward ecology-based digital Indonesian language modules. The research employed a quantitative cross-sectional survey involving 212 fifth- and sixth-grade students from an elementary school in Depok, Indonesia. Data were collected through a questionnaire developed based on the Technology Acceptance Model (TAM), focusing on ecological interest, technological perception, and students’ support toward eco-digital learning modules. The findings indicate that most students demonstrated positive responses toward the integration of ecological themes into Indonesian language learning. Ecological interest emerged as the strongest factor associated with students’ support, followed by technological perception and prior digital learning experience. Students with stronger ecological awareness and more positive perceptions of learning technology generally showed higher acceptance of eco-digital modules. However, several students still preferred contextual and experiential environmental learning activities alongside technology-based instruction. Overall, the study highlights the importance of integrating ecological literacy and accessible digital learning design in developing sustainability-oriented Indonesian language learning for elementary education.